Altered glucocorticoid reactivity and behavioral phenotype in rx3-/- larval zebrafish - Ulrich Herget; Ulrich Herget; Soojin Ryu; Soojin Ryu; Rodrigo J. De Marco; Rodrigo J. De Marco (Frontiers in Endocrinology, 2023)
IntroductionThe transcription factor rx3 is important for the formation of the pituitary and parts of the hypothalamus. Mutant animals lacking rx3 function have been well characterized in developmental studies, but relatively little is known about their behavioral phenotypes.MethodsWe used cell type staining to reveal differences in stress axis architecture, and performed cortisol measurements and behavior analysis to study both hormonal and behavioral stress responses in rx3 mutants.Results and DiscussionConsistent with the role of rx3 in hypothalamus and pituitary development, we show a distinct loss of corticotrope cells involved in stress regulation, severe reduction of pituitary innervation by hypothalamic cells, and lack of stress-induced cortisol release in rx3 mutants. Interestingly, despite these deficits, we report that rx3-/- larval zebrafish can still display nominal behavioral responses to both stressful and non-stressful stimuli. However, unlike wildtypes, mutants lacking proper pituitary-interrenal function do not show enhanced behavioral performance under moderate stress level, supporting the view that corticotroph cells are not required for behavioral responses to some types of stressful stimuli but modulate subtle behavioral adjustments under moderate stress.